A Conceptual Framework on the Role of Healing Environment in Mental Healthcare to Shape the Behavioural Health and Wellness of Urban Youth - Ni, Lim Siew; Shari, Zalina (MAJ - Malaysia Architectural Journal, 2023)
According to the United Nations (2018) data set, the world’s urban population will increase to 68% by 2050. Close to 90% of this increment occurs in Asia and Africa. Consequently, the intense urban setting has led to depression among urban youth which causes deterioration in functional wellness and a reduction in life quality . However, the current studies are only limited to the factors associated with a mental help-seeking attitude, the criteria for creating an emotionally healthy environment in mental healthcare impact that affects users' psychological behaviour are not highly emphasized. Therefore, this study aims to aims to formulate a design framework of integrating a healing environment in rebuilding mental healthcare that gives positive physical and psychological responses from youth’s perception. A qualitative method will be used to conduct interviews with the study group (urban youth and health professionals). The results are expected to lead towards background understanding of urban youth needs and the attributes of healing environment that improves youth wellness and behavioural health. The study contributes to combine different body of knowledge and contribute design framework for rebuilding mental healthcare. Future research can further investigate more variables to the existing study on aspect that can give youth positive physical and psychological responses in mental healthcare.